Extracellular Vesicles as Mediators of Environmental and Metabolic Stress Coping Mechanisms During Mammalian Follicular Development - Gebremedhn, Samuel; Ali, Asghar; Gad, Ahmed; Prochazka, Radek; Tesfaye, Dawit (Frontiers in Veterinary Science, 2020)
Extracellular vesicles are evolutionarily conserved nano-sized phospholipid membraned structures and released from virtually all types of cells into extracellular space. Their ability to carry various molecular cargos (mRNA, miRNA, proteins, and lipids) from one cell to the other to exert functional impact on the target cells enables them to play a significant role in cell to cell communication in follicular embryo development. As the molecular signals carried by extracellular vesicles reflect the physiological status of the cells of origin, they are expected to mediate any effect of environmental or metabolic stress on the growing oocyte. Accordingly, recent studies have evidenced that reproductive cells exposed to various environmental stressors (heat and oxidative stress) released extracellular vesicles enriched with mRNA and miRNA associated with stress response mechanisms. Moreover, the metabolic status of post-calving cows could be well reflected in the follicular extracellular vesicle’s miRNA profile, which signified the potential role of extracellular cellular vesicle molecular signals in mediating the effect of metabolic stress on follicular and oocyte development. In the present review, the potential role of extracellular vesicles in mediating the effect of environmental and metabolic stress in various reproductive cells and oocytes will be elucidated. Moreover, considering the importance of extracellular vesicles in shuttling protective or rescuing molecular signals during stress, their potential usage as means of targeted delivery of molecules to mitigate the effect of stress on oocytes will be the focus of future research.